2021
DOI: 10.1177/0308518x20987563
|View full text |Cite
|
Sign up to set email alerts
|

A practice ontology approach to labor control regimes in GPNs: Connecting ‘sites of labor control’ in the Bangalore export garment cluster

Abstract: In this article, I develop a practice ontology approach to labor control regimes (LCRs) in Global Production Networks (GPNs). Thereby, I address the shortcomings of existing scalar approaches to LCRs, which have not yet produced a nuanced understanding of how labor control dynamics at different scales are interrelated. Building on Schatzki’s ‘site ontology’, I conceptualize LCRs in GPNs as emerging from the networked relationships between rather localized and rather unbounded constellations of exploiting and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Generally, the studies illustrate an ongoing work control by Northern headquarters and lead firms, and limited agency of workers and trade unions in the peripheries of the global economy. This is the case, for example, in the clothing industry and food production (Cumbers, 2015; Cumbers et al, 2008; López, 2021) as well as in the programming work of the digital economy (Graham, 2019; Zook & Graham, 2018). Instead of job enrichment, teamwork and higher qualification, which are considered to be the hallmarks of post‐Fordist production and employee‐oriented work organization, there are widespread traditional patterns of labour control.…”
Section: Theoretical Concept: Mncs’ International Subsidiaries and Lo...mentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the studies illustrate an ongoing work control by Northern headquarters and lead firms, and limited agency of workers and trade unions in the peripheries of the global economy. This is the case, for example, in the clothing industry and food production (Cumbers, 2015; Cumbers et al, 2008; López, 2021) as well as in the programming work of the digital economy (Graham, 2019; Zook & Graham, 2018). Instead of job enrichment, teamwork and higher qualification, which are considered to be the hallmarks of post‐Fordist production and employee‐oriented work organization, there are widespread traditional patterns of labour control.…”
Section: Theoretical Concept: Mncs’ International Subsidiaries and Lo...mentioning
confidence: 99%
“…For many examples, however, it has been shown that the agency of the employees is extremely limited. The global competition for low production costs exerts pressure on human work, also due to (neo‐)Tayloristic work organization, especially in peripheral regions (Cumbers, 2015; López, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…of the policy transfer framework is, among others, not addressed in this paper, as further research on the continuum of policy transfer according to Dolowitz and Marsh (2000) with regard to voluntary and coercive transfer on the part of the analysed projects would be essential. 5 There is noteworthy, remarkable literature from the field of human geography reflecting on and criticizing the multilevel view which is not being considered here (see, e.g., Herod, 2008;or López, 2021).…”
Section: The Levels Of Transfermentioning
confidence: 99%
“…In turn, these policies are capable of altering business strategies, whereas LCRs are the product of the combination of work exploitation in companies and the strategies for social and spatial discipline that influence reproductive spheres (Baglioni, 2018, p. 114). Specifically, LCRs emerge from work control practices that coincide across local workplaces (López, 2021, p. 1018), especially during interaction among multi‐level processes. In developing countries, increments in local production and the consumption upsurges of supermarkets determine the trends in agricultural production, which are connected with global capital, public agenda, labour regulation, and the social reproduction of households.…”
Section: Labour Control Regimes In Global Production Networkmentioning
confidence: 99%